The Effect of MarBel Animation Media on The Ability to Recognize Numbers in Early Childhood at TK Aisyiyah Bustanul Athfal 14 - Farras, Febiana Dhimyati; Setyowati, Sri; Adhe, Kartika Rinakit; Luh, Dhian Gowinda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Technological advances in education are characterized by creation of varied learning media, for instance animation. Animation can be implemented in learning, especially for early childhood to develop children’s cognitive knowledge, such as recognizing numbers. This study aims to find out the effect of MarBel animation on the ability to recognize numbers in early childhood at Aisyiyah Bustanul Athfal 14 Kindergarten. The researcher applied quasi-experiment with one group pretest-posttest design. The sample was 15 students of Grapes Class Kindergarten B at Aisyiyah Bustanul Athfal 14 Kindergarten. Meanwhile, data collection was carried out through observation and documentation. The data analysis applied was statistics including normality tests and hypothesis tests. The results showed the Asymp. Sig. (2-tailed) value is 0.001 <0.05 which indicates H0 is rejected and H1 is accepted. Thus, it can be concluded that there is an effect of MarBel animation on the ability to recognize numbers in early childhood at Aisyiyah Bustanul Athfal 14 Kindergarten.